Developing Tourism Village Potential using Virtual Tour - Farah Putri Wenang Lusianingrum; Solehatin Ika Putri; Siti Asyisyah Aziziyah; Febrianita Putri Subandi; Muhammad Devandri (EQUATOR SINAR AKADEMIA, 2023)
The Covid-19 pandemic has had an impact on many sectors of human life, especially the tourism sector. The existence of the PSBB followed by PPKM resulted in the closure of various tourism accesses which caused a decrease in community tourism activities which resulted in a decrease in income in the tourism sector. The condition of the lack of visitors was also experienced by the Pipitan Tourism Village. In a pandemic era like this, virtual tours are a solution that can help Pipitan Tourism Village to maintain its existence so that business activities in Pipitan Tourism Village will increase again along with the increasing number of visitors. However, the Pipitan Tourism Village Pokdarwis has a problem regarding the lack of Human Resources (HR) capabilities in developing tourist attraction products. These problems have become a barrier to the progress of Pipitan Tourism Village in the digital era as it is today. This condition forms the basis that it is important to carry out assistance from the Higher Education institution using digital marketing coaching and training methods and developing tourist attraction products in the form of virtual tours.